Early outcomes of emergency ventral hernia repair in a cohort of poorly optimized patients. Issue 7 (8th June 2020) - Dissanayake, Bhanuka; Burstow, Matthew J.; Yuide, Peter J.; Gundara, Justin S.; Chua, Terence C.
Abstract: Background: Strangulated and obstructed ventral hernias require emergent repair to mitigate the risk of life‐threatening complications. Emergency ventral hernia repairs are associated with a higher rate of surgical complications and recurrence compared to elective repairs. The purpose of this study was to explore the impact of patient factors, hernia and operative characteristics on post‐operative outcomes in patients requiring emergency ventral hernia repairs. Methods: Data were collected from a prospectively held database on 86 consecutive patients undergoing emergency ventral hernia repairs between January 2016 and January 2019 at Logan Hospital. Patient, hernia and operative characteristics were collected for reporting and analysis. Results: Of the 86 patients, 29 (34%) developed a surgical complication, of which 17 patients (59%) had surgical site infections. We identified obesity ( P = 0.017), history of smoking ( P = 0.008), American Society of Anesthesiologists class of III–IV ( P = 0.008), hernia defect size ≥3 cm ( P = 0.048) and concomitant small bowel resection ( P = 0.028) to be associated with post‐operative surgical complication. Multivariate analysis identified smoking ( P = 0.005) and concomitant small bowel resection ( P = 0.026) as independent predictors for developing surgical complications. Seven patients (8%) recurred at a median of 221 days. Incisional hernias ( P = 0.001), recurrent hernias ( P < 0.001), greater than one defect ( P < 0.001) and bowel involvement ( P = 0.049) were associated with higher rates of hernia recurrence. Conclusion: Patient factors significantly influence outcomes in the emergency setting. Given that this is not modifiable at the time of surgery, greater emphasis needs to be placed on optimizing the physical and behavioural factors of patients with early symptomatic hernias for an elective repair. Abstract : Patient factors significantly influence outcomes in the emergency setting. Given that this is not modifiable at the time of surgery, greater emphasis needs to be placed on optimizing the physical and behavioural factors of patients with early symptomatic hernias for an elective repair.